PENERAPAN PEMBELAAN TERPAKSA TERHADAP PELAKU DALAM TINDAK PIDANA PENGANIAYAAN YANG MENYEBABKAN KEMATIAN (STUDI KASUS PUTUSAN PENGADILAN NEGERI PASIR PANGARAIAN NOMOR 39/PID.B/2019/PN.PRP) - Gregorius Martin; Rugun Romaida Hutabarat (Jurnal Hukum Adigama, 2022)
Noodweer is an action taken in a state of urgency. The problems faced in this study are how tojustify the perpetrators who commit crimes of persecution that cause death in the context ofself-defense and how to apply forced defense of perpetrators in criminal acts of persecution thatcause death related to the Decision of the Pasir Pengaraian District Court Number 39/Pid.B/2019/PN.Prp). The research method in this study is a normative juridical legal research method.The results showed that the justification for the perpetrators who committed the crime ofpersecution that caused death in the context of self-defense were coercive circumstances, forceddefense (noodweer), the existence of a statutory regulation and carrying out of ice orders. Theapplication of a forced defense of the perpetrator in the criminal act of persecution that causeddeath related to the Decision of the Pasir Pengaraian District Court Number39/Pid.B/2019/PN.Prp, in which in this case the perpetrator of the defense was forced to bejustified in making a forced defense due to such circumstances and conditions. that happened. Thesituation is very forced to show that there is no alternative that can be done to deal with a threat ofattack or attack because of its urgency, so it is necessary to carry out a forced defense. Thiscondition indicates that if there is a way of defending that causes less harm or no harm to theother person at all, then that method must be prioritized.